TERATOGENIK EKSTRAK ETANOL UWI BANGGAI UNGU (Dioscorea alata L.) PADA MENCIT BETINA (Mus musculus) - Ihwan Ihwan; Rahmatia Rahmatia; Khildah Khaerati (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2020)
Teratogenic is an abnormal development on embryo and is the cause of congenital defect or birth defect. This study aims to determine the effect of the addition of Dioscorea alata L. ethanol extracts to the embryo development on pregnant mice whose given orally to 24 mice which divided to 4 treatment groups, they are the normal group (NG) with NaCMC 0.5%; 28 mg/KgBB treatment group; 35 mg/KgBB; 42 mg/Kg BB. The addition of Dioscorea alata L ethanol extracts was done on the sixth day until the 15th day of pregnancy. On the 18th day of pregnancy, Laparaktomi was done to the pregnant mice and the embryo was taken out of the uterus. The observation was done to the fetus numbers, weight weighing of the fetus's body, dan length measurement of the fetus's body. Another observation is the observation of the external organ defect of the embryo. The study results that the addition of Dioscorea alata L ethanol extracts with various doses have no significant effect (P>0.5) to the mice external fetus development. On the examination of the fetus, we can conclude that Dioscorea alata L ethanol extracts don’t give any effect that may cause the defect of the fetus’ external organ.